Would Rutin be a Feasible Strategy for Environmental-Friendly Photoprotective Samples? A Review from Stability to Skin Permeability and Efficacy in Sunscreen Systems - Maíra Bueno Ariede; Wallace Androm Gomez Junior; Thalita Marcílio Cândido; Michelle Maria Gonçalves Barão de Aguiar; Catarina Rosado; Carlota de Oliveira Rangel-Yagui; Fabiana Vieira Lima Solino Pessoa; Maria Valéria Robles Velasco; André Rolim Baby (Cosmetics, 2024)
Rutin, a flavonoid found in various plants, has gained attention for its potential applications in the cosmetic industry due to its antioxidant, anti-inflammatory, and potential photoprotective properties. Our review explored the use of rutin (rutoside, 3-O-rutinoside-quercetin) in cosmetics/dermocosmetics, focusing on its physicochemical properties and stability, cutaneous permeability, and efficacy in sunscreen systems, involving in vitro tests and the current state of clinical trials. Rutin’s ability to scavenge free radicals, prevent peroxidation, and reduce vascular fragility makes this flavonoid a promising ingredient for photoprotection. Studies have shown that rutin can enhance the sun protection factor (SPF) of sunscreen formulations, especially when combined with organic UV filters. The encapsulation of rutin in nanostructures has also been investigated to improve its applicability. Overall, rutin shows potential as a safe and effective ingredient in cosmetics/dermocosmetics, offering protection against the harmful effects of UV radiation and oxidative stress on the skin, as well as being a feasible strategy for developing environmentally friendly multifunctional sunscreens.